SWOT Analysis on The Opportunity to Establish Sharia Microfinance Institutions with The Concept of Cash Waqf as an Option to Overcome Loan Sharking Activities in Traditional Fishermen - Sukaesih, Elvi (Green Publisher Indonesia, 2024)
The practice of loan sharking/middlemen in traditional fishermen activities in Ciwaru Village, Sukabumi, West Java has been going on for a long time and has been protracted. The absence of other practices besides the practices mentioned makes the Traditional Fishermen in Ciwaru Village, Sukabumi, West Java uneasy. SWOT analysis was conducted to assess the opportunity for the establishment of Sharia Microfinance Institutions with the concept of cash waqf as an alternative to the practice of loan sharks/middlemen that occur. This research uses qualitative research with field research methods and literature. The results of this study present strategies with a SWOT Matrix approach to overcome weaknesses and obstacles that are likely to occur if the establishment of Islamic Microfinance Institutions with the concept of cash endowments. Sharia Microfinance Institutions with the concept of cash waqf are very possible to be established in Ciwaru Village, Sukabumi, West Java and can be an alternative to the practice of loan sharking/middlemen in Traditional Fishermen.